One small step for man, one giant leap for men's health: a meta-analysis of behaviour change interventions to increase men's physical activity. Issue 20 (5th February 2020) - Sharp, Paul; Spence, John C; Bottorff, Joan L; Oliffe, John L; Hunt, Kate; Vis-Dunbar, Mathew; Caperchione, Cristina M
Abstract : Objective: To determine the effects of behaviour change interventions on men's physical activity (postintervention), sustained change in physical activity behaviour (≥12 months postintervention) and to identify variations in effects due to potential moderating variables (eg, theoretical underpinning, gender-tailored, contact frequency). Design: Systematic review with meta-analysis. Pooled effect size (Cohen's d ) was calculated assuming a random-effects model. Homogeneity and subsequent exploratory moderator analyses were assessed using Q, T 2 and I 2 . Data sources: Medline, EMBASE, CINAHL, SportDiscus and Web of Science to April 2019. Eligibility criteria for selected studies: Randomised control trials of behaviour change interventions in men (≥18 years) where physical activity was an outcome and data were from men-only studies or disaggregated by sex. Results: Twenty-six articles described 24 eligible studies. The overall mean intervention effect on men's physical activity was 0.35 (SE=0.05; 95% CI 0.26 to 0.45; p<0.001). This effect size is consistent with an increase of approximately 97 min of total physical activity per week or 980 steps per day. Intervention moderators associated with greater increases in physical activity included objective physical activity outcome measures, a gender-tailored design, use of a theoretical framework, shorter length programmes (≤12 weeks), using four or more types of behaviour change techniques and frequent contact with participants (≥1 contact per week). 12 studies included additional follow-up assessments (≥12 months postintervention) and the overall mean effect was 0.32 (SE=0.09; 95% CI 0.15 to 0.48; p<0.001) for that sustained increase in physical activity. Summary: Behaviour change interventions targeting men's physical activity can be effective. Moderator analyses are preliminary and suggest research directions.